The Penyuluhan Pendidikan Multikulturalisme diEra Globalisasi di SD Negeri Gungbatu Pemalang - Esty Rahmayanti (LPPM Universitas Palangka Raya, 2024)
The multicultural Indonesian nation is a potential that can be developed to improve prosperity and progress. However, this condition also has the potential to cause conflict between ethnicities, religions and cultures. Apart from that, the diversity in this country also has the potential to trigger SARA (Ethnic, Religious, Racial, Inter-Group) conflicts, this is one of the causes of damage to the unity of the Indonesian nation. However, a sense of unity and oneness is very much needed to maintain national sovereignty. SARA conflicts do not only occur in society in general but can also occur in the school environment. Therefore, multiculturalism education is needed that can provide students with an understanding of the meaning of multiculturalism in community life to create a multicultural society that respects each other and is able to live side by side peacefully (a democratic multicultural society).